2016
DOI: 10.11613/bm.2016.040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cobas 6500 and Iris IQ200 fully-automated urine analyzers to manual urine microscopy

Abstract: IntroductionUrine screening is achieved by either automated or manual microscopic analysis. The aim of the study was to compare Cobas 6500 and Iris IQ200 urine analyzers, and manual urine microscopic analysis.Materials and methodsA total of 540 urine samples sent to the laboratory for chemical and sediment analysis were analyzed on Cobas 6500 and Iris IQ200 within 1 hour from sampling. One hundred and fifty three samples were found to have pathological sediment results and were subjected to manual microscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
1
19
0
3
Order By: Relevance
“…Results showed that Sysmex UN series had satisfactory intra- and inter-assay precisions, and no carryover was detected by testing the control materials. The intra- and inter-assay precisions of Cobas 6500 were also reported as satisfactory in our previous report ( 16 ). The diagnostic accuracies of sediment analysis for both systems, compared to manual microscopy, were satisfactory.…”
Section: Resultssupporting
confidence: 75%
“…Results showed that Sysmex UN series had satisfactory intra- and inter-assay precisions, and no carryover was detected by testing the control materials. The intra- and inter-assay precisions of Cobas 6500 were also reported as satisfactory in our previous report ( 16 ). The diagnostic accuracies of sediment analysis for both systems, compared to manual microscopy, were satisfactory.…”
Section: Resultssupporting
confidence: 75%
“…Our consultations with the clinical staff at the nephrology department confirmed that higher numbers of those elements are correspondent with clinical presentation of the disease, while the lower numbers do not match the patient condition. Small number of leukocytes and erythrocytes per objective field could be found in urine sediment of healthy patients due to exercise or pregnancy ( 15 , 16 ). Errors in preanalytical phase during urine collection are fairly common and can lead to the contamination of urine sample with erythrocytes or leukocytes ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, time consuming manual microscopy is being replaced by fully automated urine analyzers ( 19 , 24 ). These systems are quickly becoming part of routine work in both large and small laboratories as a fast way to exclude urine samples from healthy individuals, increase productivity and reduce inter-observer variability ( 16 , 19 , 24 , 25 ). However, manual examination of urine sediment is still part of routine practice in many European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Urine cytology is useful in the detection and diagnosis of various benign diseases and conditions such as infections of different etiologies, and in distinguishing hematuria from the upper and/or lower urinary tract. In addition, it is useful in detecting inflammation in the bladder and kidney (Caleffi and Lippi, 2005;Bottini et.el., 2005;Bakan et. al., 2016;Alatzas et.al., 2012;Sikirica et.…”
Section: Introductionmentioning
confidence: 99%
“…Credit for the scientific development in research of urinary corpuscular elements over the past 10 years goes to the automated analyzers or automated microscopy, or more specifically, to the flow cytometry and digital imaging systems (Anderlini et al, 2015;Bakan et al, 2016;Bogaert et al, 2016;Oyaert, and Delanghe, 2018). However, the total accuracy of these instruments in identifying (erythrocytes, leukocytes, epithelial cells, casts) is questionable.…”
Section: Introductionmentioning
confidence: 99%